Exploring the Role of Inflammatory Cytokines and Oxidative Stress in Febrile Seizure Pathogenesis: A Case-Control Study in Mumbai, India - Lakshmi Srivanathan; Saeed Khan (Scientific Journal of Pediatrics, 2024)
Introduction: Febrile seizures (FS) are the most common childhood seizure disorder, often causing parental anxiety and posing a challenge for healthcare professionals. While the exact pathogenesis remains unclear, recent research suggests a complex interplay of genetic predisposition, fever, and inflammatory processes. This study aimed to investigate the role of inflammatory cytokines and oxidative stress markers in FS pathogenesis among children in Mumbai, India. Methods: A case-control study was conducted involving 100 children with FS (cases) and 100 age-matched febrile children without seizures (controls) admitted to a tertiary care hospital in Mumbai. Serum levels of inflammatory cytokines (IL-1β, IL-6, TNF-α, and IL-10) and oxidative stress markers (malondialdehyde [MDA] and superoxide dismutase [SOD]) were measured and compared between the two groups. Results: Children with FS exhibited significantly higher serum levels of pro-inflammatory cytokines IL-1β, IL-6, and TNF-α (p<0.001 for all) compared to controls. Conversely, the anti-inflammatory cytokine IL-10 was significantly lower in the FS group (p<0.001). Furthermore, MDA levels were significantly elevated (p<0.001), while SOD levels were significantly decreased (p<0.001) in the FS group compared to controls. Conclusion: This study provides evidence for the involvement of inflammatory cytokines and oxidative stress in FS pathogenesis. Elevated pro-inflammatory cytokines and oxidative stress markers, coupled with decreased anti-inflammatory cytokine levels, suggest a dysregulated inflammatory response and impaired antioxidant defense mechanism in children with FS.